IFIP International Federation for Information Processing
DOI: 10.1007/978-0-387-74909-9_16
|View full text |Cite
|
Sign up to set email alerts
|

CAT Platform for Analogue and Mixed-Signal Test Evaluation and Optimization

Abstract: This paper introduces a Computer-Aided-Test platform that has been developed for the evaluation of test techniques for analogue and mixed-signal circuits. The CAT platform, integrated in the Cadence Design Framework Environment, includes tools for fault simulation, test generation and test optimization for these types of circuits. Fault modeling and fault injection are simulator independent, which makes this approach flexible with respect to past approaches. In this paper, the use of this platform is illustrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Using a built-in test technique for an RF LNA as a casestudy, we have shown that the new approach is more accurate than previous approaches, circumventing limitations that arise due to the arbitrary form of the output parameter distributions and the dimensionality of the output space. In addition, this method is very fast and simple to implement and it has been included in an existing mixed-signal/RF Computer-Aided-Test (CAT) platform [20].…”
Section: Discussionmentioning
confidence: 99%
“…Using a built-in test technique for an RF LNA as a casestudy, we have shown that the new approach is more accurate than previous approaches, circumventing limitations that arise due to the arbitrary form of the output parameter distributions and the dimensionality of the output space. In addition, this method is very fast and simple to implement and it has been included in an existing mixed-signal/RF Computer-Aided-Test (CAT) platform [20].…”
Section: Discussionmentioning
confidence: 99%
“…They encapsulate tools (e.g., fault extractor or analogue simulator) and facilitate execution of the DOT flow [17] [18]. We use NXP's internal tool DOTSS (defect oriented test simulation system) in this work [19].…”
Section: Previous Workmentioning
confidence: 99%
“…. , 6 are computed using the fault simulator developed in [18], [19]. Note that the simulation results obtained in [18] 10 5 ].…”
Section: Case-studymentioning
confidence: 99%